Determination of Vitamin C in Fresh Fruits and Vegetables Using the Dye-titration and Microfluorometric Methods - E. S., Tee; S. I., Young; S. K., Ho; S., Siti Mizura (1988)
The vitamin C content of19 types of fresh fruits and 24 vegetables was determined by the official AOAC methods of dye-titration and microfluorometry. As expected, values obtained by the latter method, which estimated ascorbic acid plus dehydroascorbic acid (DHAA), were clearly higher than those given by the titration method, which determined only ascorbic acid. There were considerable differences in the values obtained by the two methods, depending on the concentration ofDHAA in the foods. Larger differences were obtained for the vegetables. The mean recovery value obtained by the dye-titration method was significantly higher than that given by the fluorometric method (p <0.01). Reproducibility studies showed that the two methods did not give significantly different variances (p < 0.05). If only ascorbic acid values were required, the titrimetric procedure would give good results, and it may be ca"ied out rapidly using simple laboratory equipment. If a fluorometer was available, total vitamin C values, which would be more useful from the nutritional point of view, could be determined.